2015
DOI: 10.1016/j.dsr2.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Global habitat preferences of commercially valuable tuna

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 87 publications
(135 reference statements)
7
138
1
1
Order By: Relevance
“…Here, we found that the minimum preferred value was 4.4 ml.l −1 (196 mmol.m −3 ) which is consistent with previous findings, noting that the present study area is smaller and in this case, the threshold relates to preference not survival. The preferred range for MLD ranged from 6 to 158 m and is consistent with the distributions found by Arrizabalaga et al (2015) and Tanabe et al (2017). Our observed minimum limit appears to be near the extreme observed level.…”
Section: Habitat Characteristics Of Skipjack Tuna and Their Ecologicasupporting
confidence: 75%
See 4 more Smart Citations
“…Here, we found that the minimum preferred value was 4.4 ml.l −1 (196 mmol.m −3 ) which is consistent with previous findings, noting that the present study area is smaller and in this case, the threshold relates to preference not survival. The preferred range for MLD ranged from 6 to 158 m and is consistent with the distributions found by Arrizabalaga et al (2015) and Tanabe et al (2017). Our observed minimum limit appears to be near the extreme observed level.…”
Section: Habitat Characteristics Of Skipjack Tuna and Their Ecologicasupporting
confidence: 75%
“…The preferred SST range we identified (21.6-30.0 • C) is nearly identical to the extreme SST range measured at-sea by the French purse seine fleet at SKJ set locations (21.5-30.0 • C; IRD, unpublished data). A similar range was also obtained from the fishery-independent (Lopez et al, 2017) and fishery-dependent based preference models developed for SKJ (Andrade, 2003;Arrizabalaga et al, 2015;Tanabe et al, 2017). For O 2 , Barkley et al (1978) found that a minimum value of 3-3.5 ml.l −1 (134-156 mmol.m −3 ) was necessary for the long-term survival of SKJ while Arrizabalaga et al (2015) found that a value around 3.8 ml.l −1 (170 mmol.m −3 ) was preferred by for SKJ across the world's oceans.…”
Section: Habitat Characteristics Of Skipjack Tuna and Their Ecologicamentioning
confidence: 99%
See 3 more Smart Citations